On Others as Evil - Charles E. Butterworth (International Institute of Islamic Thought, 1996)
The first part of this essay’s title is inspired by the antepenultimate speech of Garcin in Sartre’s famous play Huis Clos or No Exit: So that’s what Hell is. I never would have believed it . . . You remember: sulphur, pyre, the grill. . . Ah! what a joke. There’s no need for a grill; Hell is Others.’ Given the tendency these days for differing parties to turn every encounter with their interlocutor4eir other-away from what could be a fruitful discussion and reduce it to a series of mutual recriminations, Garcin’s insight seems especially apt. Yet when the discussion concerns the West as contrasted to the Middle East, even Christianity or Judaism as contrasted to Islam, there is far too much for each interlocutor to learn from the other to dwell so on bygone slights, especially since those slights arise from the very ignorance that exploration of our different ways-exchange in the best sense of the term-should overcome. For exchange to be fruitful, each party needs to look at the best in his or her own tradition, rather than at the worst, or even the ordinary, and to ask that the interlocutor do the same for his or her tradition. Like Homer, we can begin by praying for inspiration of sorts: Tell me Muse, of the man of many ways, who was driven far journeys, after he had sacked Troy’s sacred citadel. But like the wily, ever devious, as well as unremitting curious and farsighted Odysseus of whom Homer sings, we need then to reflect on the things we see and experience. Odysseus is a man well-traveled, a man of broad experience-albeit not entirely by his own choosing. Were it not that he never abandons the desire to regain his homeland and hearth, to arrive at the happiness he understands to be truly his, he might even be called multicultural. After all, Homer also says the following of him: Many were they whose cities he saw, whose minds he learned of, many the pains he suffered in his spirit on the wide sea, struggling for his own life and the homecoming of his companions ...